A REVIEW OF RECENT RESEARCH IN INDOOR MODELLING & MAPPING - Gunduz, M.; Isikdag, U.; Basaraner, M. (COPERNICUS GESELLSCHAFT MBH, 2016)
Indoor modeling and mapping has been an active area of research in last 20 years in order to tackle the problems related to positioning and tracking of people and objects indoors, and provides many opportunities for several domains ranging from emergency response to logistics in micro urban spaces. The outputs of recent research in the field have been presented in several scientific publications and events primarily related to spatial information science and technology. This paper summarizes the outputs of last 10 years of research on indoor modeling and mapping within a proper classification which covers 7 areas, i.e. Information Acquisition by Sensors, Model Definition, Model Integration, Indoor Positioning and LBS, Routing & Navigation Methods, Augmented and Virtual Reality Applications, and Ethical Issues. Finally, the paper outlines the current and future research directions and concluding remarks.
Keywords: Indoor; Mapping; Modelling; Navigation; IFC; CityGML; IndoorGML; BUILDING MODELS; SYSTEMS; Computer Science; Physical Geography; Remote Sensing